2020
DOI: 10.1101/2020.04.07.029496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for the binding of SNAREs to the multisubunit tethering complex Dsl1

Abstract: Multisubunit tethering complexes (MTCs) are large (250 to >750 kDa), conserved macromolecular machines that are essential for SNARE-mediated membrane fusion in all eukaryotes. MTCs are thought to function as organizers of membrane trafficking, mediating the initial, long-range interaction between a vesicle and its target membrane and promoting the formation of membrane-bridging SNARE complexes. Previously, we reported the structure of the Dsl1 complex, the simplest known MTC, which is essential for COPI-mediat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…The binding affinity between Num1CC and Mdm36 is very similar to other tethering factors, and the affinity might be strong enough not to be fallen apart during mitochondrial fission. It should be noted that the binding affinity of the multisubunit tethering complex Dsl1 and soluble N-ethylmaleimide-sensitive factor attachment protein receptor was similar to that of the Num1CC-Mdm36 complex (Travis et al, 2020). Furthermore, the ITC experiment also indicated that the stoichiometry of Num1CC and Mdm36 was 1:1, which was consistent with the results previously anticipated by the SEC-MALS experiment (Fig.…”
Section: Biochemical Characterization Of the Num1-mdm36 Complexsupporting
confidence: 90%
“…The binding affinity between Num1CC and Mdm36 is very similar to other tethering factors, and the affinity might be strong enough not to be fallen apart during mitochondrial fission. It should be noted that the binding affinity of the multisubunit tethering complex Dsl1 and soluble N-ethylmaleimide-sensitive factor attachment protein receptor was similar to that of the Num1CC-Mdm36 complex (Travis et al, 2020). Furthermore, the ITC experiment also indicated that the stoichiometry of Num1CC and Mdm36 was 1:1, which was consistent with the results previously anticipated by the SEC-MALS experiment (Fig.…”
Section: Biochemical Characterization Of the Num1-mdm36 Complexsupporting
confidence: 90%